Is young age a limiting factor when training balance? Effects of child-oriented balance training in children and adolescents - Wälchli, M.; Ruffieux, J.; Mouthon, A.; Keller, M.; Taube, W. (Pediatric Exercise Science, 2018)
Purpose: Balance training (BT) studies in children reported conflicting results without evidence for improvements in children under the age of 8. The aim of this study therefore was to compare BT adaptations in children of different age groups to clarify whether young age prevents positive training outcomes. Methods: The effects of 5 weeks of child-oriented BT were tested in 77 (38 girls and 39 boys) participants of different age groups (6-7 y, 11-12 y, and 14-15 y) and compared with age-matched controls. Static and dynamic postural control, explosive strength, and jump height were assessed. Results: Across age groups, dynamic postural sway decreased (-18.7%; P=.012; 2p=.09) and explosive force increased (8.6%; P=.040; 2p=.06) in the intervention groups. Age-specific improvements were observed in dynamic postural sway, with greatest effects in the youngest group (-28.8%; P=.026; r=.61). Conclusion: In contrast to previous research using adult-oriented balance exercises, this study demonstrated for the first time that postural control can be trained from as early as the age of 6 years in children when using child-oriented BT. Therefore, the conception of the training seems to be essential in improving balance skills in young children.